Dietary restriction: Metabolic shifting for cardiac health - Faine, L. A.; Cicogna, A. C.; Diniz, Y. S.; Almeida, J. A.; Burneiko, R. C.; Rodrigues, H. G.; Novelli, E. L. B. (Taylor & Francis, 2003)
Purpose: To determine the effect of dietary restriction on metabolic pathways and the relationship of the metabolic shifting on antioxidant enzymes in cardiac tissue. Design: Randomized, controlled study. Male rats at 60 days old were randomly divided into four groups. Materials and Methods: The rats of control groups C30 and C60 were given free access to the diet over 30 and 60 days. The rats of the DR30 group were fed 60% of the chow consumed by the control groups over 30 days. The animals of the DR60 group ate 60% of the amount consumed by the C60 group over 60 days. Serum was used for total protein, lactate dehydrogenase (LDH), alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Protein, glycogen, total lipids, superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), LDH, AST and ALT were determined in cardiac tissue. Results: Dietary restriction induced diminished serum and cardiac LDH activities. AST activities were lower in the serum and cardiac muscle of the DR60 animals. Dietary restriction induced elevated total lipid concentrations in cardiac muscle. No significant differences were observed in total protein and glycogen content among the groups. Antioxidant enzyme determinations demonstrated increased cardiac GSH-Px activities in the DR60 animals and increased SOD activities in the cardiac tissue of both feed-restricted groups. Conclusions: Dietary restriction was protective against oxidative stress in the heart by improving cardiac endogenous antioxidant defences and shifting the metabolic pathway for energy production.
Keywords: Cardiac health; Dietary restriction; Metabolism; Oxidative stress; antioxidant; enzyme; glutathione peroxidase; glycogen; plasma protein; protein; superoxide dismutase; alanine aminotransferase blood level; animal experiment; aspartate aminotransferase blood level; clinical pathway; controlled study; diet restriction; eating; enzyme activity; food intake; health; heart; heart function; heart muscle; lactate dehydrogenase blood level; lipid blood level; lipid metabolism; metabolism; nonhuman; priority journal; rat; Animalia